Reproductive Disorders and Subsequent Fertility in Primiparous and Multiparous Holstein–Friesian Cows - Syah, H. A.; Susilawati, T.; Rifa’i, M.; Yekti, A. P. A.; Isnaini, N.; Mashudi; Susilorini, T. E.; Suyadi; Utami, P.; Pramudhita, A. D. (Tropical Animal Science Journal, 2026)
Reproductive disorders, including abortion, retained placenta, and dystocia, are significant challenges in dairy cows which can negatively affect reproductive efficiency, particularly in tropical smallholder farming systems. Therefore, this study aimed to evaluate the effects of abortion, retained placenta, and dystocia on subsequent reproductive performance in Holstein-Friesian cows and compare the effects between primiparous and multiparous animals raised under smallholder conditions. Data were collected from 415 cows, namely 40 healthy primiparous, 68 healthy multiparous, 18 primiparous and 32 multiparous with abortion, 47 primiparous and 67 multiparous with dystocia, and 71 primiparous and 72 multiparous with retained placenta. Reproductive parameters included first service conception rate (FSCR), pregnancy rate (PR), overall pregnancy rate (OPR), services per conception (S/C), days to first service (DFS), and open days (DO). Two-way binary logistic regression was applied to categorical variables, and analysis of variance (ANOVA) in a General Linear Model (GLM) was used for continuous variables. Kaplan–Meier survival analysis was performed to compare DFS and DO among disorder groups. Cows with reproductive disorders showed numerically lower FSCR, PR, and OPR, as well as higher S/C, compared with healthy counterparts, and these differences were not statistically significant (p>0.05). Kaplan–Meier analysis detected shorter mean DFS and DO among affected cows despite the reduced hazard for pregnancy. Although the effects were not statistically significant, the numerical patterns suggested potential biological relevance. The results showed the importance of effective postpartum management to maintain optimal reproductive performance in smallholder dairy systems.